2009
DOI: 10.1021/ef800636f
|View full text |Cite
|
Sign up to set email alerts
|

Waxy Gels with Asphaltenes 1: Characterization of Precipitation, Gelation, Yield Stress, and Morphology

Abstract: We examine the effects of asphaltenes upon the crystallization behavior of a model waxy oil. Yield stress measurements on the model waxy oils with asphaltenes isolated from Shengli crude oil showed that both the relative amount of wax to asphaltenes and the aggregation state of the asphaltenes affected the crystallization properties of the wax. At very low asphaltene concentrations and high wax concentrations, the yield stress of the waxy gel is not significantly affected. At higher asphaltene concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
131
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 44 publications
16
131
1
Order By: Relevance
“…It has been reported that flocculated asphaltenes providing nucleation sites for waxes increase WAT [44], but also it has been reported [30] that asphaltenes decreased very slightly the WAT. According with other studies [45] the effect of the asphaltenes on the WAT depends of the aggregation state of the asphaltenes.…”
Section: Dsc Study Of the Effect Of Asphaltenes On Liquid-solid Phasesupporting
confidence: 51%
“…It has been reported that flocculated asphaltenes providing nucleation sites for waxes increase WAT [44], but also it has been reported [30] that asphaltenes decreased very slightly the WAT. According with other studies [45] the effect of the asphaltenes on the WAT depends of the aggregation state of the asphaltenes.…”
Section: Dsc Study Of the Effect Of Asphaltenes On Liquid-solid Phasesupporting
confidence: 51%
“…In the current section, gelation was determined by using oscillatory tests as proposed by others (Webber 2001;Venkatesan et al 2003;Coutinho 2004, 2007;Kané et al 2004;Visintin et al 2005;Magda et al 2009;Tinsley et al 2009;Phillips et al 2011). Low-amplitude and low-frequency oscillating shear strain was applied to the oil specimen within the linear viscoelastic region.…”
Section: Gelation Temperaturementioning
confidence: 99%
“…In other words, in the presence of amidic-functionalised waxes there is a greater tendency for re-arranging a solid internal structure where the solid-like units are made by alternation and association of wax crystals and asphaltene molecules. On the other hand, this is not the first time that similar associations and interactions are observed or hypothesised in bituminous materials and oils (Pauli et al, 2011;Thanh, Hsieh, & Philp, 1999;Tinsley et al, 2009).…”
Section: The 'Hot' Case Of Amidic-modified Bitumen or Tendency Towardmentioning
confidence: 59%
“…Nevertheless, the chemical nature of wax in bitumen is not so simple and somehow conflicts or complies with the conceptual origin of asphaltenes (Redelius, 2009;Tinsley, Jahnke, Dettman, & Prud'homme, 2009). Many studies were carried out about the nature of petroleum waxes and their effects on bitumen quality.…”
Section: Introductionmentioning
confidence: 99%